Education Provision in Zimbabwe: The Return of the Ghost of Stratification and Its Implications to Quality and Access in Education. - Jenjekwa, Vincent (2022)
At independence in 1980, the new majority government of Zimbabwe embarked on an ambitious but necessary programme to expand education provision as well as remove bottlenecks and other discriminatory practices which the colonial government had pursued. Issues of access and quality in education took centre stage as the new government sought to fulfil promises made during the protracted liberation struggle. In the first two decades of Zimbabwe’s independence, significant strides were made in dealing with inequalities in the way schoolchildren at secondary school were treated. Resources were poured towards provision of education in previously disadvantaged communities under the new government’s policy of education for all. However, with the economic challenges which Zimbabwe faced after the year 2000, stratification in education provision re-emerged in ways reminiscent of the discriminatory colonial era education system. As of now the majority of urban and rural day schools, resettlement or so called satellite schools, where the majority of Zimbabwean schoolchildren attend school, grapple with severe shortages of human and material resources and this has serious implications on access and quality in education. The paper contends that unless government intervenes to arrest the ever increasing gap in terms of educational quality and access between elite schools and ordinary secondary schools which cater for the majority of children, stratification in the provision of education will have telling consequences on national development in Zimbabwe. The research was carried out with a representative sample of five secondary schools from Masvingo district through analysis of documents, observations and interviews of critical stake holders in the schools